From Private Counsellor to Public Church Politician – Three Female Expressions of Conservative, Urban Lutheranism in Western Sweden, 1810–1910 - Jarlert, Anders (Studies in church history, 1998)
During the nineteenth century, the High Church revival tradition initiated by Henric Schartau (1757-1825) was widely spread and accepted in western Sweden. According to Bishop Wordsworth of Salisbury, Schartau ‘had something of the character of Dr. Pusey in his relation to those who consulted him, but, in his position at Lund, and his general influence, he was perhaps more like his English contemporary, Charles Simeon (1759-1836), at Cambridge’. Wordsworth found great merit in his teaching, being ‘strong and spiritual, and without the defects of Moravian or Pietistic sentimentality’. During his Scandinavian journey in 1889, Randall Davidson characterized the followers of Schartau as a High Church party in their emphasis on private confession and their strict rules of conduct. On the other hand he found them to be zealous about the Sabbath, and preaching conversion in a quasi-Methodist way. Here, we shall study this movement through the examples of three women of urban culture. The Schartau tradition has been studied mainly with emphasis on its doctrines and clergy, and as a rural tradition connected to the unchanging values and structures of the old rural society. Through these examples of urban women, the general impact of the tradition is widened, and the emphasis is put on the changes in reception of the tradition among lay people in a changing society.